Study the Anti-Hyperlipidemia Effects of Ambrosia Maritime in Albino Female Rats and their Fetus - Majeed, Zainab Hasan; Ismail, Rajaa Mosa (American Journal of Biology and Natural Sciences, 2025)
The aim of current study is investigation the anti-hyperlipidemia effects of Ambrosia maritime in albino female rats and their fetus. In this experiment 30 male rats (wt 140-160 gm with age 12-16 weeks) at a period April to Augustus 2021. The rats divided to four experimental groups. The present findings show that the concentration of total protein and albumin in high fat diet (HFD) group significant (P < 0.05) reduce compared with control group. Otherwise, total cholesterol, triglyceride and malonedialdehyied (MDA) in HFD group show significant (P < 0.05) elevate compared with control group. While, catalase show significant (P < 0.05) decrease in HFD group compared with control group. After using leaves extract of A. maritime in tratmnet, the levels of all above parameters show improvement in their levels. Therefore, it can be concluded that the leaves extract of A. maritime show anti-hyperlipidemia activity in current experiment. In the livers of fetal obese rats, a decrease was found in the number of hematopoietic megakaryocytes, along with a decrease in hematopoietic elements. Anucleated nuclei and nucleated nuclei were observed in the sinusoids, which appeared in smaller numbers compared to the control group. In the extract group, the central vein and normal hepatocytes were found, as well as the sinusoidal arrangement between the hepatocytes. In the treated group, the normal shape of the central vein, normal hepatocytes, and the sinusoidal arrangement between the hepatocytes were found. An improvement was also observed in the number of hematopoietic megakaryocytes. it can be concluded that the leaves extract of A. maritime show anti-hyperlipidemia activity in current experiment. On the other hand, it was found that A. maritime dosage is highly effective in improving the liver tissue of fetuses, due to its possession of many active compounds, including phenols and flavonoids.